Pre-prosthetic minor tooth movement with elastic separating ring & provisional restoration modification: case report - Haneol Shin; Byoung-Duck Roh; Yoo-Seok Shin; Chan-Young Lee (Korean Academy of Conservative Dentistry, 2012)
Proximal caries or coronal defect in posterior teeth may result in the loss of proximal space and drifting of neighboring teeth, which makes restoration difficult. Inability to restore proper contours and to align tooth axis properly are commonly encountered problems when planning tooth restoration. Moreover, tilted teeth aggravate periodontal tissue breakdown, such as pseudo-pocket, and angular osseous defect. The purpose of this case presentation is to describe a simple technique for inducing minor tooth movement with orthodontic separating ring and provisional restoration modification. This method was used to create crown placement space on mesially tilted molar. This method is easy, simple and efficient technique which could be used in interproximal space gaining in selected situation.